The lipopeptides fengycin and iturin are involved in the anticandidal activity of endophytic Bacillus sp. as determined by experimental and in silico analysis. (1st August 2022) - Banerjee, S.; Sen, S.; Bhakat, A.; Bhowmick, A.; Sarkar, K.
Abstract: In this study, an endophytic Bacillus sp. strain (K7) was isolated from the medicinally important ornamental plant, Jasminum officinale. Biochemical analyses were conducted to evaluate the nature of the extracted product, which displayed strong anticandidal activity against Candida albicans (CA) SC5314, as evident from the results obtained in agar‐cup diffusion tests, phase‐contrast microscopy, scanning electron microscopy and minimum inhibitory concentration assays. After confirming the presence of the gene clusters encoding the lipopeptides iturins and fengycin in the genome of K7, their corresponding molecular ions were identified using MALDI‐TOF‐MS. 3D structures of the lipopeptides were downloaded from specific databases and molecular docking was performed against a vital CA enzyme, exo‐1, 3‐beta‐glucanase, involved in cell wall remodelling, adhesion to polymer materials and biofilm formation. The docking score of iturins was found to be −8·6 and −8·2 kcal mol −1 and for fengycin it was −9·4 kcal mol −1, indicating a strong affinity of these cyclic lipopeptides towards exo‐1, 3‐beta‐glucanase. The combined in vitro and in silico anticandidal studies suggested that these secreted lipopeptides from Bacillus sp. may be used as potential therapeutics against opportunistic and complicated infections of CA. Abstract: Significance and Impact of the Study: In the fight against complicated Candida infections, we have explored the ability of bacterial endophytes to control human diseases. One such isolate belonging to Bacillus sp. was found to inhibit Candida albicans SC5314, in vitro, by producing cyclic lipopeptides iturins and fengycins. Using molecular docking, the fengycins and iturins produced by the Bacillus were shown to bind to the active site of exo‐1, 3‐beta‐glucanase of the pathogen, resulting in enzyme inhibition causing possible cell weakening and death. Considering that thousands of endophyte species are available in nature and are unexplored, our research presents the medical relevance of these organisms to the global scientific community.